KEMAMPUAN PENALARAN MATEMATIS PESERTA DIDIK BERDASARKAN DIMENSI BERNALAR KRITIS - Purwanto, Zaene Alifia; Yusmin, Edy; Yani T, Ahmad (Academy of Education Journal, 2023)
Mathematical reasoning ability is one of the five standard processes in mathematics learning. There is a need for ability when learning mathematics, thus is considered important for the government to design education with a curriculum that can facilitate students to develop abilities either in mathematics learning or other learning. One of the government's efforts in designing education in Indonesia is to design a curriculum, namely the Kurikulum Merdeka, in which there is a project to strengthen the Profil Pelajar Pancasila. There are 6 (six) dimensions in the Profil Pelajar Pancasila, one of those is Dimensi Bernalar Kritis which is assumed to be closely related to the mathematical reasoning ability needed in learning mathematics. In this article, we will discuss the meaning of mathematical reasoning ability and the dimension of critical reasoning. In addition, it will be explored whether there is a relation between mathematical reasoning ability and Dimensi Bernalar Kritis and whether Dimensi Bernalar Kritis can be used to measure mathematical reasoning ability.